Review of Studies on Recognition Technologies and Their Applications Used to Assist Learning and Instruction - Rustam Shadiev; Zi Heng Zhang; Ting-Ting Wu; Yueh Min Huang (Educational Technology & Society, 2020)
We reviewed studies on recognition technologies published in the last ten years. This review study was aimed toward identifying, appraising, selecting, and synthesizing all high quality research evidence published in the literature related to recognition technologies and on determining how they can assist learning and instruction. This study particularly focuses on summarizing the current state of knowledge in the following dimensions: (1) recognition technology and processes, (2) applications, (3) schemes, and (4) advantages and disadvantages. We reviewed seventy-two papers and identified eighteen recognition technologies. Our results showed that all of the recognition technologies under consideration featured different recognition processes and applications. In most studies, the participants were university students. Questionnaires and tests were the most frequently used data collection methods. Most studies used a group comparison as their research design. Finally, several advantages and disadvantages of the recognition technologies were identified and summarized in the papers. The most frequently cited disadvantage was a low recognition accuracy rate. Based on our results, several suggestions and implications are made for the teaching and research community.